2014
DOI: 10.1128/mbio.00928-13
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Removal of Bacterial Strains by Use of Genome-Targeting CRISPR-Cas Systems

Abstract: CRISPR (clustered regularly interspaced short palindromic repeats)-Cas (CRISPR-associated) systems in bacteria and archaea employ CRISPR RNAs to specifically recognize the complementary DNA of foreign invaders, leading to sequence-specific cleavage or degradation of the target DNA. Recent work has shown that the accidental or intentional targeting of the bacterial genome is cytotoxic and can lead to cell death. Here, we have demonstrated that genome targeting with CRISPR-Cas systems can be employed for the seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
317
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 359 publications
(340 citation statements)
references
References 58 publications
(92 reference statements)
14
317
2
7
Order By: Relevance
“…S4 A and B) (25). Transformation with plasmids eliciting chromosomal self-targeting by CRISPR-Cas systems appeared cytotoxic as measured by the relative reduction in surviving transformants compared with non-self-targeting plasmids (15,29). Targeting the lacZ gene in S. thermophilus resulted in an ∼2.5-log reduction in recovered transformants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S4 A and B) (25). Transformation with plasmids eliciting chromosomal self-targeting by CRISPR-Cas systems appeared cytotoxic as measured by the relative reduction in surviving transformants compared with non-self-targeting plasmids (15,29). Targeting the lacZ gene in S. thermophilus resulted in an ∼2.5-log reduction in recovered transformants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Vercoe et al (30) demonstrated that chromosomal targeting by a type-IF CRISPR-Cas system caused elimination of a horizontally acquired pathogenicity island in Pectobacterium atrosepticum (30). The concept of sequence-based removal of specific genotypes was developed further as a tool for manipulation of microbial consortia via CRISPR-Cas targeting, resulting in directed genome evolution at the population level (15). In accordance with previous work, our results demonstrate that wild-type clones were removed from the population, but mutants without CRISPR-Cas-targeted features survived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies, and another study (13), also showed that the transferred CRISPR-Cas system is capable of eliminating specific bacterial populations. Furthermore, they demonstrated that the system might be used against pathogens to effectively treat infected animals.…”
mentioning
confidence: 87%
“…CRISPR-Cas systems have also recently been used to phenotypically correct genetic diseases in live animals (11), and their utility is being explored for various therapeutic approaches in mammals. Nevertheless, only limited studies have shown the use of CRISPR-Cas systems to target antibiotic resistance genes or a specific population of virulent bacterial strains (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%